2006
DOI: 10.1001/archsurg.141.10.1000
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Neuroendocrine Hepatic Tumors

Abstract: Background: The optimal treatment for hepatic metastases from neuroendocrine tumors remains controversial because of the often indolent nature of these tumors. We sought to determine the effect of 3 major treatment modalities including medical therapy, hepatic artery embolization, and surgical resection, ablation, or both in patients with liver-only neuroendocrine metastases, with the hypothesis that surgical treatment is associated with improvement in survival.Design: Retrospective study.Setting: Tertiary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(80 citation statements)
references
References 8 publications
3
77
0
Order By: Relevance
“…However, the overall survival after hepatic resection has been reported in 46-86% at 5 years and 35-79% at 10 years (49,59,60,61,62,63,64,65,66,67,68,69,70,71,72). This wide heterogeneity reflects the selection bias that is present in the majority of series.…”
Section: Surgery Of Lmmentioning
confidence: 99%
“…However, the overall survival after hepatic resection has been reported in 46-86% at 5 years and 35-79% at 10 years (49,59,60,61,62,63,64,65,66,67,68,69,70,71,72). This wide heterogeneity reflects the selection bias that is present in the majority of series.…”
Section: Surgery Of Lmmentioning
confidence: 99%
“…However, unlike other gastrointestinal malignancies, surgical intervention is considerably more effective, and removal of both the metastasis and primary tumour is often considered if technically feasible in patients of excellent performance status, either in a synchronous or staged resection. Various groups have reported impressive 5-year survival rates up to 87% following surgical resection of NET liver metastases (Que et al 1995, Chamberlain et al 2000, Nave et al 2001, Musunuru et al 2006. Unfortunately recurrence is observed in the majority of patients (Cho et al 2008).…”
Section: Surgerymentioning
confidence: 99%
“…Concerning other prognostic parameters for primary NETs and liver metastases, Katz et al demonstrated that the robust presence of tumor-infiltrating lymphocytes is a significant predictor of outcome [44]. Other recent articles confirmed surgical therapy to be the most efficient approach against solitary hepatic metastases [7,8,14,22,23,33,34,40,45,46], with a potential curative resection of liver secondaries can be undertaken in 13.7 to 24.5% of patients with metastatic NETs [47][48][49], and a significant reduction of carcinoid symptoms [43], but the majority of studies focused exclusively on resection rather than combined-modality approaches with ablation or chemotherapy.…”
Section: Liver Metastases From Neuroendocrine Tumorsmentioning
confidence: 99%
“…In fact, metastases are well recognized as being the major cause of death among neoplastic patients, and the prognosis of patients affected by unresectable liver metastases is very poor. However, although once metastatic malignancies were commonly considered as a terminal neoplastic stage, nowadays, many different therapeutical options have been introduced in order to provide a safe and efficient treatment for these kinds of patients and improve both their quantity and quality of life [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%